2021
DOI: 10.2147/jhc.s330301
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Therapy Reduces Mortality in Hepatocellular Carcinoma Patients with Low-Level Hepatitis B Viremia

Abstract: Background and Aims: Although antiviral treatment has been shown to reduce mortality in hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) patients with high HBV-DNA levels, it is still unclear whether it is useful in reducing mortality in patients with low HBV-DNA levels. Methods: A retrospective analysis of 756 HBV-associated HCC patients at the Beijing Ditan Hospital with HBV-DNA levels < 500 IU/mL was conducted between January 2008 and June 2017. Patients were divided into antiviral and non-ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In this study, HCC patients who received preoperative AVT demonstrated superior liver function reserve, which may contribute to better OS. 29 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, HCC patients who received preoperative AVT demonstrated superior liver function reserve, which may contribute to better OS. 29 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to various costs, requisite parameters and non-parameters for the Markov decision-tree model in this study included the clinical transfer probabilities between states and the utility values corresponding to each state [14][15][16]. These values were meticulously curated from pertinent research, with probabilities, costs, and utilities [17][18][19][20][21]. The optimal path selection for the decision analysis was scrutinized employing the rollback method, a technique facilitating the retrospective tracing of total costs and treatment outcomes resulting from the implementation of distinct strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional treatment for HBV replication is extensively used due to its efficacy, few side effects, high tolerance, and once-daily dosing. While most patients responded well to lamivudine, the treated group had mortality rates of 18% to 40%[ 131 , 132 ]. The study found that non-responders had decompensated liver disease before therapy.…”
Section: Management Strategies For Hbv Reactivationmentioning
confidence: 99%